On the ground among the beasts, under the whisper of the stars: contributions to a zoopoetic reading of franz kafka’s work - Ricardo Gil Soeiro (Estudios de Teoría Literaria)
Franz Kafka (1883‑1924) is one of the most influential authors in universal literature. Cultivating an unmistakable style, Kafka's work as a whole — composed, for the most part, of incomplete or posthumously published books — explores the feeling of absurdity that punctuates the ontological ambiguity of the human being, divided between the individual dimension and the universal scope, between the tragic and the comic, between the absence of meaning and the realm of rationality and logic. From the nakedness of his prose comes an unsettling strangeness that gives his narratives an implacable lucidity. Subscribing to the validity of the different theoretical angles that have been used to read Kafka's work, the present study aims, however, to deepen a line of research that only recently has been touched upon with the required profundity. Anchoring myself in conceptual approaches with a post-anthropocentric approach (Deleuze/Guattari, 2003; Derrida, 2006; Geier, 2016; Harel, 2020), I will examine a set of Zoopoetics mechanisms that Kafka sets in motion in Die Verwandlung, alluding to other of his stories about animals (the so-called Tiergeschichten), seeking to understand how a posthumanist prism proves capable of illuminating some of the meanings that Kafka's texts reveal, promoting, in a broadly nuanced way, a process of decentering of the human – a strategic vector for the posthumanist forma mentis.